Research theme mapping and future directions on corruption and religion: a bibliometric analysis - Salahudin; Taqwa Sihidi, Iradhad; Roziqin, Ali; Dwi Cahyani, Tinuk; Karinda, Kisman; Firdaus, Muhammad; Baharuddin, Tawakkal (Frontiers in Sociology, 2025)
Corruption harms social and economic structures whilst religion acts as a moral pillar with ethical values to fight it. Unfortunately, the relationship between the two is less explored in the literature. This present study employs a bibliometric analysis approach with data retrieved from the Scopus database. We explore the relationship between corruption and religion through the identification of trends and mapping important topics to reveal potential future research on the topic. The results show a considerable increase in the recent number of publications on the topic despite its limited literature. More importantly, the mapping illustrates that the relationship between corruption and religion has transformed focus from economic, social, and political factors to including religious variables as an important element. In particular, topics like religiosity, religious affiliation, liberation theology, education, and anti-corruption mark shifts in complexity in current discussions. Such a complexity challenges diverse perceptions of religious values and their position in linking political and economic interests. This finding implies that future research needs to adopt a holistic and contextual framework to understand the factual impact of religion on corruption. This attempt potentially expands the current thinking on the role of religion within corruption cases in shaping a more inclusive perspective that bridges anti-corruption practises in society.